A New Model to Explain the Alignment of Certain Ancient Sites - Carlotto, Mark (Journal of Scientific Exploration, 2020)
In a previous study of over two hundred ancient sites, the alignments of almost half of the sites could not be explained. These sites are distributed throughout the world and include the majority of Mesoamerican pyramids and temples that are misaligned with respect to true north, megalithic structures at several sites in Peru’s Sacred Valley, some pyramids in Lower Egypt, and numerous temples in Upper Egypt. A new model is proposed to account for the alignment of certain unexplained sites based on an application of Charles Hapgood’s hypothesis that global patterns of climate change over the past 100,000 years could be the result of displacements of the Earth’s crust and corresponding shifts of the geographic poles. It is shown that over 80% of the unexplained sites reference four locations within 30° of the North Pole that are correlated with Hapgood’s hypothesized pole locations. The alignments of these sites are consistent with the hypothesis that if they were built in alignment with one of these former poles they would be misaligned to north as they are now as the result of subsequent pole shifts.